Dipole relaxation, dielectric and electric properties of PbWO₄ crystals - Shevchuk, V.N.; Kayun, I.V. (Functional Materials, 2005)
Experimental dependences of permittivity for undoped PbWO₄ single crystals at 1 kHz frequency in 290-550 К temperature range are considered. The ε(Т) curve runs under heating and cooling are different. The ε(Т) function under heating is characterized by groups of narrow maxima at 290-330 К and 330-400 К, the former being predominating. At 400-470 К, the ε(Т) dependence is linear, while above 470 К, the function is nearly exponential. After the high-temperature heat treatment of a sample, a multistage relaxation process of ε values within limits of 25 to 30 is observed at 290 К. The features of ε(Т) at low temperatures are defined by the dipole polarization and hopping mechanism of the charge exchange between complex dipole associates. The pairs of lead and oxygen vacancies (dipolons) are predominating intrinsic defects of the crystal structure; those defects form more complex dipole associates.